Dyadic influences on awareness of condition in people with dementia: findings from the IDEAL cohort - Alexander, Catherine M.; Martyr, Anthony; Gamble, Laura D.; Quinn, Catherine; Pentecost, Claire; Morris, Robin G.; Clare, Linda (Frontiers in Aging Neuroscience, 2023)
Introduction The discrepancy between caregiver-ratings and self-ratings of abilities is commonly used to assess awareness in people with dementia. We investigated the contribution of caregiver and dyadic characteristics to the difference in perspective between caregiver-informants and people with dementia about difficulties experienced, when considering awareness of condition. Methods We conducted exploratory cross-sectional analyses using data from the IDEAL cohort. Participants were 1,038 community-dwelling people with mild-to-moderate dementia, and coresident spouse/partner caregivers. The Representations and Adjustment to Dementia Index (RADIX) checklist reporting difficulties commonly experienced in dementia was completed by 960 caregiver-informants and 989 people with dementia. Difference in scores was calculated for 916 dyads. Demographic information, cognition, informant-rated functional ability and neuropsychiatric symptoms were recorded for the person with dementia. Self-reported data were collected on mood, comorbidity, religion, importance of religion, relationship quality, and caregiver stress. Results For most dyads, caregivers reported more RADIX difficulties than people with dementia. Caregiver RADIX ratings were more closely associated with informant-rated functional ability and neuropsychiatric symptoms than with cognition. More RADIX difficulties and higher stress were reported by female caregivers. Greater RADIX difference was associated with more caregiver stress, and older age but less depression in people with dementia. Conclusion Few dyadic characteristics were important, but caregiver stress was higher where caregivers reported more RADIX difficulties and/or the difference in perspective was greater, whereas partners with dementia reported better mood. In addition to offering information about awareness of condition, the caregiver rating and difference in perspectives could indicate where more support is needed.